Spirooxadiazoline oxindoles: synthesis and evaluation of anticancer and antimalarial activities - Lopes, Elizabeth de Abreu (2020)
Cancer is one of the modern world’s most common and deadly non-infectious disease. According to WHO Cancer Report of 2015, it is one of leading causes of morbidity and mortality worldwide with 8.8 million deaths in 2015 and it is expected to rise about 70% over the next 20 years. The non-selectivity and acute toxicity of many anticancer agents has prompted the search for new alternatives with improved tumour selectivity, efficiency and safety. Spirooxindole alkaloids are a family of natural products that have a spiro ring fusion at position 3 of the oxindole core. Several natural products that possess this heterocyclic core, such as alstonisine, horsfiline, strychnofoline and spirotryprostatin A and are described as having interesting bioactivities. These scaffolds have been described with different biological activities, including in vitro anticancer activities in several cancer cell lines. In this thesis, we report the development of a novel library of spirooxadiazoline oxindoles derivatives with an [1,3,4]-oxadiazole ring and evaluation of its anticancer and antimalarial activities. With this goal, twenty spirooxadiazoline oxindole compounds were synthesized by reaction of isatin derivatives and nitrile imines (formed in situ from the corresponding hydrazonyl chlorides), in moderate to high yields (42-90%). The anti-proliferation activity of this library was tested in two breast cancer cell lines, MCF-7 and MDA-MB-231, at a concentration of 50 μM. In MCF-7, the p53 retains wild type conformation and in MDA-MB-231, the p53 protein has the mutation R280K. Five compounds showed to inhibit around 40-50% the cancer cells growth, at 50 μM concentration. Two of them showed to act in both tested cell lines, other two compounds showed to be more selective for MDA-MB-231 cell line and one showed to be selective for MCF-7 cell line. These five compounds show the importance of some substituents such as the meta-substituted phenyl ring in position 3’, the substitution in position 5 and the alkyl group in position 5’. Comparing the anti-proliferation activity of this library with its regioisomer, the [1,2,4]-oxadiazole scaffold shows higher inhibition of cancer cells growth than the [1,3,4]-oxadiazole scaffold, for both cancer lines. This can be explained by the different position of the substituents in space that fill the binding site. It has been reported that some compounds, for example artemisinin, have both anticancer and antimalarial activity. For this reason, this family was also tested in Plasmodium falciparum strains, W2 and 3D7. Six compounds showed to be very potent for a chloroquine-resistant strain (W2), with IC50 values between 1.4 and 9.0 μM. In addition, two compounds showed to be potent for both chloroquine resistant and sensitive strains, W2 and 3D7, respectively. Overall, in this work it is reported for the first time the synthesis of a new family of spirooxadiazoline oxindoles. It is also the first time reported 1,3-dipolar cycloadditions by reacting the hydrazonyl chlorides with isatin derivatives, reducing the number of reaction steps. The anti-proliferative activity is also reported for the first time in two breast cancer cell lines and, more importantly, the discovery that these small molecules represent useful compounds for the development of novel antimalarials.